Novel Synthesis and Characterization of Nanostructured Materials - Kopp Alves, Annelise; Bergmann, Carlos P.; Berutti, Felipe Amorim; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
Nanostructured materials have been largely studied in the last few years. They have great potential of applications in different fields such as materials science, physics, chemistry, biology, mechanic and medicine. Synthesis and characterization of nanostructured materials is a subject of great interest involving science, market, politicians, government and society. Based on results obtained by the authors' research group during the past decade, this book comes to present novel techniques to synthesize nanostructured materials and characterize their properties such as crystallinity and crystallite size, specific surface area, particle size, morphology and catalytic activity. This book is aimed for students, researchers and engineers searching for methodologies to obtain and characterize nanostructures in details.
Combustion synthesis -- Spray pyrolysis -- Electrospinning -- CCVD Synthesis of Carbon Nanotubes and Carbon Nanotubes Forests -- Hydrothermal synthesis -- High-energy milling.
Keywords: Surfaces (Physics).; Materials Science; Characterization and Evaluation of Materials; Ceramics, Glass, Composites, Natural Methods; Nanoscale Science and Technology